On names of tourist facilities in Roztocze – Naming procedures and the marketing context - Siwiec, Adam (Papers in Linguistics, 2023)
The main aim of the study is to show various forms of nominations and applications of onyms in tourist marketing. Thus, it was necessary to identify the most important naming tendencies in the context of particular modes of name modelling and functions they perform in communication with recipients of the message. The analysed names refer to a variety of facilities; they exhibit characteristics of chrematonyms and, at the same time, they can function as oikonyms (names of buildings) in the process of nominalization. All the onyms referred to here can perform marketing tasks, but to a varying degree. The information they convey is most often given directly, and the denotation-based meaning in this case includes clear elements of facilities’ description (related, for example, to their location and landscape), which, in turn, can to some extent be combined with the valuation found in tourist offers. A persuasive, or simply advertising function is manifested thus both in onyms that fit into recognisable structural and content models, and those that may be classified as more original. The latter arise as a result of formal linguistic creation or through a selection of semantic elements that build the message about a given place. The impact resulting from this persuasive-advertising strategy can be seen in the case of names of hotels and similar establishments so far rarely encountered in Roztocze which make use of newer and foreign naming patterns, attributed to the spread of English.